A Grasshopper Optimization-based fault-tolerant control algorithm for a human occupied submarine with the multi-thruster system. (15th December 2021) - Zhu, Danjie; Wang, Lei; Hu, Zhen; Yang, Simon X.
Abstract: An intelligent fault-tolerant control (FTC) strategy is proposed to resolve the power loss problem for the multi-thruster system fault of the manned submarine. The proposed FTC is developed on basis of the Grasshopper Optimization Algorithm (GOA), where GOA is applied to reallocate the thruster forces when they encounter damages (power loss) of different degrees in fault cases. The reallocated forces are restricted within the physical constraints of the thruster outputs, and meanwhile are optimized to derive the torques as desired to sustain the ideal movement of the vehicle for achieving a robust controlling result. Simulations under different fault cases and comparisons to other FTCs demonstrate the effectiveness and the efficiency of the proposed GOA based FTC strategy. Highlights: Configure the problem of power loss for a late-model human-occupied submarine. Resolve the power loss of different levels under various and even extreme faults. Increase accuracy/efficiency of the fault-tolerant control results.